Beethoven, from Bruckmann's portrait collection - Munich : Friedr. Bruckmann's Verlag (2026)
Postcard depicting portrait of Beethoven by Fritz Schwörer, published by Friedr. Bruckmann's Verlag. 1 print on cardstock : engraving ; 17 x 11.5 cm. (6.75 x 4.5 in.).